SYNTHETIC BIOLOGY AND ARTIFICIAL MEAT: A SOLUTION TO THE FOOD CRISIS - Svetlana Ilyinichna Kim (Western European Studies, 2024)
This article explores the role of synthetic biology in addressing the global food crisis through the development of artificial meat. With the rising demand for sustainable and ethical food production, synthetic biology offers innovative solutions by engineering cells to produce cultured meat. The paper examines the environmental, economic, and ethical advantages of artificial meat, highlighting its potential to reduce reliance on traditional livestock farming. Key technologies, including cell culture, tissue engineering, and bioreactors, are discussed alongside real-world examples and case studies demonstrating the scalability of artificial meat production
Keywords: synthetic biology; artificial meat; food crisis